2024
DOI: 10.1186/s13287-023-03619-7
|View full text |Cite
|
Sign up to set email alerts
|

Critical contribution of mitochondria in the development of cardiomyopathy linked to desmin mutation

Yeranuhi Hovhannisyan,
Zhenlin Li,
Domitille Callon
et al.

Abstract: Background Beyond the observed alterations in cellular structure and mitochondria, the mechanisms linking rare genetic mutations to the development of heart failure in patients affected by desmin mutations remain unclear due in part, to the lack of relevant human cardiomyocyte models. Methods To shed light on the role of mitochondria in these mechanisms, we investigated cardiomyocytes derived from human induced pluripotent stem cells carrying the h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 103 publications
0
2
0
Order By: Relevance
“…The study demonstrated fewer cristae that could explain the decrease in the expression of COXIV, a mitochondrial respiratory chain protein (Hovhannisyan et al, 2024). Furthermore, RNA sequencing showed that iPSC-CMs with the E439K mutation show downregulation of genes that are related to mitochondria, compared to control cells (Hovhannisyan et al, 2024).…”
Section: Concerning Ventricular Tachyarrhythmias Results Obtained Inmentioning
confidence: 89%
See 1 more Smart Citation
“…The study demonstrated fewer cristae that could explain the decrease in the expression of COXIV, a mitochondrial respiratory chain protein (Hovhannisyan et al, 2024). Furthermore, RNA sequencing showed that iPSC-CMs with the E439K mutation show downregulation of genes that are related to mitochondria, compared to control cells (Hovhannisyan et al, 2024).…”
Section: Concerning Ventricular Tachyarrhythmias Results Obtained Inmentioning
confidence: 89%
“…When studying how the p.E439K desmin variant may affect mitochondria in cardiomyocytes derived from human induced pluripotent stem cells (iPSC-CMs), Hovhannisyan et al concluded that not only are mitochondria physically altered but also functionally. The study demonstrated fewer cristae that could explain the decrease in the expression of COXIV, a mitochondrial respiratory chain protein (Hovhannisyan et al, 2024). Furthermore, RNA sequencing showed that iPSC-CMs with the E439K mutation show downregulation of genes that are related to mitochondria, compared to control cells (Hovhannisyan et al, 2024).…”
Section: Concerning Ventricular Tachyarrhythmias Results Obtained Inmentioning
confidence: 89%